2021
DOI: 10.17219/acem/134021
|View full text |Cite
|
Sign up to set email alerts
|

EGCG decreases myocardial infarction in both I/R and MIRI rats through reducing intracellular Ca2+ and increasing TnT levels in cardiomyocytes

Abstract: Background. Myocardial ischemia/reperfusion injury (MIRI) usually induces serious health problems.Objectives. This study attempted to explore protective effects of (−)-epigallocatechin-3-gallate (EGCG) on MIRI and the associated mechanism. Materials and methods.Ischemia/reperfusion of an isolated rat heart (I/R model) and the MIRI model were used in this study. Myocardial infarction was measured with staining with 2,3,5-triphenyltetrazolium chloride (TTC). Ca 2+ and troponin T (TnT) concentrations in coronary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…A meta-analysis of 15 studies, involving 231 animals 16, [19][20][21]23,25,26,[28][29][30][31][32][33]35,36 , showed that the EGCG treatment signi cantly reduced the myocardial infarct size (IS) compared to controls (SMD=-4.06; 95% CI: -5.17, -2.94; P < 0.01; I 2 = 77%) (Fig. 2a).…”
Section: Myocardial Infarct Sizementioning
confidence: 99%
See 1 more Smart Citation
“…A meta-analysis of 15 studies, involving 231 animals 16, [19][20][21]23,25,26,[28][29][30][31][32][33]35,36 , showed that the EGCG treatment signi cantly reduced the myocardial infarct size (IS) compared to controls (SMD=-4.06; 95% CI: -5.17, -2.94; P < 0.01; I 2 = 77%) (Fig. 2a).…”
Section: Myocardial Infarct Sizementioning
confidence: 99%
“…The effects of EGCG on serum biomarkers of myocardial injury were evaluated by creatine kinase (CK), creatine kinase isoenzyme (CK-MB), lactic dehydrogenase (LDH), and troponin T (TnT). Four publications involved 64 animals utilizing CK 13,14,18,26 , 6 publications involved 112 animals utilizing CK-MB 13,22,24,32,33,37 , 8 publications involved 132 animals utilizing LDH 13,18,[24][25][26]31,33,37 , and 2 publications involved 24 animals utilizing TnT 24,30 , as the outcome measure. Compared to controls, EGCG signi cantly reduces serum CK (SMD=-4.66; 95% CI: -6.72, -2.59; P < 0.01; I 2 = 73%; Fig.…”
Section: Cardiac Enzymesmentioning
confidence: 99%